EFFECTS OF CEILING FANS ON THE THERMAL COMFORT OF STUDENTS IN LEARNING ENVIRONMENTS OF BAYERO UNIVERSITY, KANO, NIGERIA - M. ALI, SANI; MARTINSON, BRETT D.; AL-MAIYAH, SURA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
It is well known that thermal comfort is influenced by major physical parameters; air and radiant temperatures, humidity, and air speed in combination with personal attributes; clothing insulation and activity level. Although temperature is conventionally considered in adaptive thermal comfort model, as the most important physical parameter where cooling is involved, moderate air speed can enhance thermal comfort during higher temperatures. Through convective and evaporative cooling, ceiling fans cool people by causing sweat from the occupant’s body to evaporate. The northern part of Nigeria, being in the tropics, is known for higher temperature regimes for most part of the year. The use of air conditioning to achieve thermal comfort is not sustainable, for economic reasons and the lack of stable electrical energy. Therefore, a majority of naturally ventilated spaces could be kept thermally comfortable with the control of ceiling fans and operable windows. As part of a research work on learning environments in a Northern Nigerian university, this study reports on the effects of ceiling fans on the thermal comfort perception of the students in two lecture theatres. In addition to the measurements of air speed, air and radiant temperatures, relative humidity, a comfort survey was also undertaken in the spaces, from which activity levels and clothing insulations were obtained. Adaptive thermal comfort standards, ASHRAE 55 and EN 15251, state that thermal comfort can be maintained as air temperature rises with the use of ceiling fans operating at moderate speed. The results from this study show that reductions of 31% and 22% in overheating from the two lecture theatres were realised, as a result of ceiling fans usage, measured by the degree hour’s exceedance indicator. These results were further corroborated by the students’ acceptance of thermal conditions of the lecture theatres at temperatures above Tmax.